Identification Of Problems At Medicine Procurement In Hospital A Literature Review - Solihah, Inganatus; Diah Ayu Puspandari; Satibi (Journal of Mandalika Literature, 2025)
Medicine procurement in hospitals still faces various issues that hinder drug availability. This study aims to identify problems in the medicine procurement process. The methodology employed is a literature review from various sources, including international databases. The results indicate that the main issues include the absence of a drug formulary system, inconsistencies in disease patterns, and improper planning methods. The conclusion of this study emphasizes the need for improvements in the management of medicine procurement to ensure better availability in hospitals. Keywords: Medicine Procurement; Hospitals; Problems.